2016
DOI: 10.1177/1203475416683389
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Ultraviolet Radiation Safety Measures for Outdoor Workers

Abstract: Ultraviolet radiation (UVR) poses a major risk for outdoor workers, putting them at greater risk for skin cancer. In the general population, the incidence of both melanoma and nonmelanoma skin cancers is increasing. It is estimated that 90% of skin cancers in Canada are directly attributable to UVR exposure, making this cancer largely preventable with the appropriate precautions. A scoping review was conducted on the barriers and facilitators to UVR safety in outdoor workers to elucidate why these precautions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…These findings also highlight scope for developments in the way that sunscreen is made available with a view towards altering perceptions concerning ease of use. Our findings are consistent with those of studies showing that outdoor workers perceive a host of issues, including inconvenience, as barriers to occupational sunscreen application [37]. The availability of pocket-sized single-application sachets might encourage reapplication during delivery rounds.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings also highlight scope for developments in the way that sunscreen is made available with a view towards altering perceptions concerning ease of use. Our findings are consistent with those of studies showing that outdoor workers perceive a host of issues, including inconvenience, as barriers to occupational sunscreen application [37]. The availability of pocket-sized single-application sachets might encourage reapplication during delivery rounds.…”
Section: Discussionsupporting
confidence: 90%
“…Farmers in the Midwestern United States similarly identified inconvenience as a disincentive to wearing a wide-brimmed hat, with 45% of survey respondents reporting such a hat gets in the way of their work [36]. A review of the literature on barriers to the wearing a wide-brimmed hat when working in the sun found that baseball-style caps were preferred by the majority of outdoor workers and these served to keep the sun out of the eyes, leaving little impetus for change [37]. These results highlight an imperative for the development of a hat suitable for company-wide distribution that provides shade to the face, the ears, and the neck without obstructing vision and remaining fashionable.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, shade seeking at midday may not be practical in some situations (i.e., roadside construction), and may also be discouraged because of employer perceptions (i.e., lost productivity or financial constraints) (14). To confront these barriers, several studies have reported that it is important for workplaces to establish a culture that promotes prevention, including resources for protection, employee training, and policy or mandates (13,(27)(28)(29). Participants in a qualitative study on the barriers to and facilitators of sun safety interventions discussed the importance of senior-level engagement in workplace health promotion (30).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the USPSTF does recommend interventions aimed at education and prevention. Messaging and preventative efforts for skin cancer have been devised and implemented on a local, national, and international level with direct patient intervention and policy changes to decrease the skin cancer burden [ 6 – 15 ].…”
Section: Introductionmentioning
confidence: 99%